UJI BERBAGAI MACAM PUPUK ORGANIK CAIR TERHADAP PERTUMBUHAN DAN HASIL TANAMAN PADI - WIYONO WIYONO; ACHMAD FATCHUL AZIEZ (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2007)
The object of reseacch was the effect kind of liquid organic fertilizers and the kind concentration to the grown and yield of rice plant.